A study on the effect of inclined magnetic field and Hall current on the micropolar fluid model of blood flow through stenotic arteries in a porous medium. (2018) - Dar, Ajaz Ahmad; Elangovan, K.
The problem of blood flow through a horizontal non-symmetric artery with a mild stenosis in a porous medium has been investigated. The natures of blood in small arteries are analysed mathematically by considering it as a homogeneous and incompressible micropolar fluid. The effect of both rotation and inclined magnetic field are studied analytically and computed numerically. To evaluate the influence of the stenosis shape, an appropriate geometry has been considered such that the shape of the stenosis can be changed simply just by varying a parameter (referred to as the shape parameter). The expressions for the flow characteristics such as velocity, the impedance (resistance to flow), the wall shear stress distribution and its magnitude at the stenosis throat have been derived and analysed for different values of shape parameter n, rotation parameter Ω, the magnetic field parameter M, inclination angle of the magnetic field parameter ( θ ), permeability parameter ( K 1 ), the coupling number N and the micropolar fluid parameter m .